Metal–organic frameworks with 5,5′-(1,4-xylylenediamino) diisophthalic acid and various nitrogen-containing ligands for selectively sensing Fe( iii )/Cr( vi ) and nitroaromatic compounds - Xu, Cungang; Bi, Caifeng; Zhu, Zheng; Luo, Rong; Zhang, Xia; Zhang, Dongmei; Fan, Chuanbin; Cui, Liansheng; Fan, Yuhua (CrystEngComm, 2019)
Four novel Zn( ii ) metal–organic frameworks (MOFs) including {[Zn(L) 0.5 (bimb)]·2H 2 O·0.5(CH 3 ) 2 NH} n ( 1 ), {[Zn(L) 0.5 (bimmb)]·2H 2 O} n ( 2 ), {[Zn(L) 0.5 (btdpe)]·H 2 O} n ( 3 ), and [Zn(L) 0.5 (bidpe)] n ( 4 ) (H 4 L = 5,5′-(1,4-xylylenediamino) diisophthalic acid, bimb = 1,4-bis(imidazol-1-yl)-butane, bimmb = 1,4-bis(imidazol-1-ylmethyl)benzene, btdpe = 4,4′-bis(4 H -1,2,4-triazol-4-yl)diphenyl ether, and bidpe = 4,4′-bis(imidazolyl)diphenyl ether) were solvothermally prepared and further characterized by elemental analysis, IR spectroscopy, single-crystal X-ray diffraction, thermogravimetric (TG) analysis and powder X-ray diffraction (PXRD). Single-crystal X-ray diffraction analysis showed that complex 1 features a 3-fold interpenetrated bbf topological framework with the Schläfli symbol of (6 4 ·8 2 )(6 6 ) 2 . Complex 2 displayed an unprecedented 2-nodal (4,4)-connected 3D framework with the Schläfli symbol of (8 6 ), while complexes 3 and 4 showed 3-nodal (2,4,4)-connected (4·8·10 4 ) 2 (4) 2 (8 4 ·10·12)-unprecedented frameworks. Luminescence studies revealed that complexes 1–4 can be used as high selectivity luminescence sensors for sensing Fe( iii ) cations, Cr( vi ) anions (Cr 2 O 7 2− and CrO 4 2− ) and nitroaromatic compounds. Furthermore, a possible sensing mechanism was investigated in this paper.